2018
DOI: 10.1029/2018ja025450
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Radio Emissions Associated With Terrestrial Gamma‐Ray Flashes

Abstract: In this study, we analyze 44 terrestrial gamma‐ray flashes (TGFs) detected by the Fermi Gamma‐ray Burst Monitor (GBM) occurring in 2014–2016 in conjunction with data from the U.S. National Lightning Detection Network (NLDN). We examine the characteristics of magnetic field waveforms measured by NLDN sensors for 61 pulses that occurred within 5 ms of the start‐time of the TGF photon flux. For 21 (out of 44) TGFs, the associated NLDN pulse occurred almost simultaneously with (that is, within 200 μs of) the TGF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
(105 reference statements)
1
20
1
2
Order By: Relevance
“…But the TGF source altitude range of 10–15 km is consistent with all of the events. Note that the TGF source altitude range of 10.613.9 km in case 6 is consistent with the LMA VHF source altitudes reported by Mailyan et al () and Lyu et al () for the same event.…”
Section: Analysis and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…But the TGF source altitude range of 10–15 km is consistent with all of the events. Note that the TGF source altitude range of 10.613.9 km in case 6 is consistent with the LMA VHF source altitudes reported by Mailyan et al () and Lyu et al () for the same event.…”
Section: Analysis and Resultssupporting
confidence: 90%
“…Fermi GBM detected a TGF at 21:23:43.910235 UT on 4 September 2015 (also discussed in Mailyan et al, , and Lyu et al, ). The Fermi geographic footprint was 24.69 °N, −83.06 °E while the satellite altitude was 541.55 km.…”
Section: Analysis and Resultsmentioning
confidence: 78%
“…In an effort to understand how EIPs are produced and gain insight into TGF generation, we have presented sub-microsecond VHF radio mapping of an EIP, providing over an order of magnitude finer temporal detail than previously reported TGF-related VHF observations (Lu et al, 2010;Lyu et al, 2016Lyu et al, , 2018Mailyan et al, 2018). Given that EIPs can serve as proxy for a subpopulation of TGFs (Cummer et al, 2017;Lyu et al, 2016), and that the observed EIP sferic developed independently from the VHF emissions generally associated with streamer activity (Liu et al, 2019;Rison et al, 2016;Shi et al, 2016Shi et al, , 2019, our study provides strong evidence that the EIP sferic was not produced by conventional lightning processes (i.e., streamers and leaders), but by the relativistic electrons and associated ionization of a TGF-producing discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relativistic runaway electron avalanche process (Dwyer, 2003;Gurevich et al, 1992) is widely accepted, additional mechanisms such as the thermal electron runaway model (Carlson et al, 2010;Celestin & Pasko, 2011) or the relativistic feedback processes (Dwyer, 2003(Dwyer, , 2008(Dwyer, , 2012 are thought to be required. Besides gamma-ray observations, ground-based radio-frequency (RF) measurements provide insights into the TGF-producing mechanism (Abbasi et al, 2018;Cummer et al, 2014Cummer et al, , 2015Lu et al, 2010;Lyu et al, 2016;Mailyan et al, 2018). Source location and altitude estimated by RF measurements are useful to investigate the total number of avalanche electrons in TGFs (Dwyer & Cummer, 2013;Cummer et al, 2014Cummer et al, , 2015Mailyan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%